Implementation of Relating, Experiencing, Applying, Cooperating, Transferring (REACT) Model to Students Learning Achievement in Chemical Basic Law Material at 10th Grade Students of SMA Negeri 1 Kalasan - Ristanti Cahyaningrum; Beta Wulan Febriana (Universitas Islam Indonesia, 2019)
This study aimed to determine the significant differences of learning achievement at 10th grade students of SMA Negeri 1 Kalasan between the application of conventional learning models with learning models Relating, Experiencing, Applying, Cooperating, Transferring (REACT) in the domain of knowledge, attitudes, and skill on the Basic Chemical Law materials. This study also aimed to know students’ response to learning using REACT model. This research was an experimental using Quasi Experimental Design, namely Posttest Only with Nonequivalent Groups Design. The population in this study was all students of 10th grade SMA 1 Kalasan in the academic year 2017/2018. This study used two classes as the study sample. The data were analyzed using Independent Samples T-Test parametric test for the knowledge and attitude domain, and Mann Whitney U non parametric test for the skill domain. The results of this study can be concluded that (1) there was no significant difference in student learning achievement in the knowledge domain, (2) there was no significant difference in student learning achievement in the attitude domain, and (3) there was significant differences in student learning achievement in the skill domain between the application of conventional learning models with REACT learning models in the Chemical Basic Law and (4) students gave a good response to the REACT learning model performed.